2009
DOI: 10.1111/j.1750-3841.2009.01206.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural Formation of Styrene by Cinnamon Mold Flora

Abstract: Tests on 106 dried pure cinnamon samples of diverse origins showed that some samples were naturally contaminated with high levels of styrene, up to 524 microg/g. Styrene taint can be associated with high water activity levels and thus with microorganism growth. The mold flora of a Korintji cinnamon sample in which styrene had been found at a 50 microg/g concentration was analyzed and 5 species of mold were isolated. An investigation into the ability of the 5 species of mold to produce styrene showed that 3 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Penicillium sp. isolated from cinnamon samples converted cinnamon related compounds to styrene (Lafeuille et al, 2009). Styrene is also produced by other fungal species such as Penicillium caseifulvum (Larsen, 1998) and Trichoderma on potato dextrose broth with aromatic cinnamic acid added (Pinches and Apps, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Penicillium sp. isolated from cinnamon samples converted cinnamon related compounds to styrene (Lafeuille et al, 2009). Styrene is also produced by other fungal species such as Penicillium caseifulvum (Larsen, 1998) and Trichoderma on potato dextrose broth with aromatic cinnamic acid added (Pinches and Apps, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…10 SM has been shown a breakdown product formed by cinnamon mold ora and possibly may be present in oceans as a single contaminant. 16 But SOs with constant composition ratio (puri ed PS decomposition, SM1: SD1: ST5 and eld survey in this study, SM1: SD1: ST8) is not naturally present in ocean. It is clear that SO contamination has been around for 45 years before.…”
Section: Worldwide Sos Contaminationmentioning
confidence: 65%
“…Concerning cinnamic acid, one of the most studied pathways is the non-oxidative decarboxylation of cinnamic acid to styrene. It occurs in fungi, such as Aspergillus, Penicillium, and Trichoderma [40][41][42]. When assayed OMWW, some fungal strains showed different trends, as the most resistant fungi were Ao and Pp [6]; however, An and Lt, which were the most promising strains in this research, also showed the ability to grow on media containing OMWW with a high content of phenol.…”
Section: Removal Of Cinnamic or Vanillic Acid In Liquid Mediamentioning
confidence: 68%